Audit fee and digital transformation: Managerial ownership impact on sustainability - Adianto, Rachmad Satrio; Choiriah, Siti (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
This study examines the impact of Audit Fees and Digital Transformation on Sustainability Performance with Managerial Ownership as Moderation. The populace in this research were energy businesses that are listed on the Indonesia Stock Exchange (IDX) in 2020-2023, totaling 90 companies. The sampling design Purposive sampling was employed so that the an example used was 34 businesses. The method of analysis used was panel data using the eviews 13 for linear regression analysis tool. The outcomes of the study simultaneously showed that Audit Fees and Digital Transformation had an effect on Sustainability Performance. Partially, it showed that audit fees had an positive effect on sustainability performance, but digital transformation had no effect on sustainability performance. The moderating variable, namely managerial ownership, could moderate audit fees on sustainability performance, but could not moderate digital transformation on sustainability performance.